Prevalence of stroke in adults over 40 years of age, who consulted a public hospital in Paraguay, from January to June 2024 - Toro Persch , Maria Eduarda; Soares Teixeira, Letícia; Monteiro Gomes, Fabyana Rossany; Pérez Velilla, María Adela (International Journal of Neurology, 2025)
Introduction: Stroke is a common cause of disability and death. It occurs when blood flow to the brain is interrupted due to a damaged blood vessel, leading to oxygen and nutrient deficiency, causing paralysis and permanent damage, especially in people with other pathologies. Objectives: To determine the prevalence of stroke in the population over 40 years of age, from January to June, in a public hospital in Paraguay. Materials and methods: An observational, descriptive, retrospective, and cross-sectional study was conducted, the sample consisted of 45 patients. Results and discussion: Regarding the temporal distribution, the month with the most cases was April, with 14 patients (31.1%). Regarding sex, males predominated with 26 cases (57.8%). Regarding age, the most frequent age group was 62–72 years (35.6%). The most common district of residence was Villa Elisa, with 27 patients (60%). The predominant symptoms were dyspnea, dizziness, dysphagia, and hypertension. Regarding diagnosis, 12 patients had ischemic stroke (26.7%), 7 were diagnosed with hemorrhagic stroke (15.6%), and in 8 cases the etiology was undetermined (17.8%). In 16 patients (35.5%), stroke occurred as a secondary episode to associated diseases. Conclusion: The findings show that stroke mainly affects elderly men residing in Villa Elisa, with a predominance of ischemic stroke and a high frequency of associated comorbidities. Therefore, it is essential to strengthen prevention strategies and timely diagnosis in the at-risk population.